Uric acid and diabetes risk among Chinese women with a history of gestational diabetes mellitus. (December 2017) - Leng, Junhong; Wang, Leishen; Wang, Jing; Li, Weiqin; Liu, Huikun; Zhang, Shuang; Li, Lili; Tian, Huiguang; Xun, Pengcheng; Yang, Xilin; Yu, Zhijie; Hu, Gang
Highlights: Serum uric acid was positively associated with the risks of type 2 diabetes. Serum uric acid was positively associated with the risks of prediabetes. The association of uric acid and diabetes risk was influenced by body mass index. We examined among Chinese women with prior gestational diabetes after delivery. Abstract: Aims: To assess the association of uric acid (UA) with the risks of postpartum type 2 diabetes and prediabetes among women with prior gestational diabetes mellitus (GDM). Methods: We performed a cross-sectional study of 1262 GDM women at 1–5 years after delivery using the baseline data from the Tianjin Gestational Diabetes Mellitus Prevention Program. Logistic regression models were used to estimate the association of different levels of serum UA with the risks of type 2 diabetes and prediabetes. Results: The multivariable-adjusted odds ratios (ORs) across quartiles of serum UA were 1.00, 1.23 (95% confidence interval [CI] 0.55–2.78), 2.05 (95% CI 0.96–4.39), and 3.17 (95% CI 1.54–6.55) (Ptrend  < 0.001) for type 2 diabetes, and 1.00, 1.50 (95% CI 1.03–2.19), 2.28 (95% CI 1.58–3.30), and 2.88 (95% CI 1.99–4.17) (Ptrend  < 0.001) for prediabetes, respectively. Restricted cubic splines models showed positive linear associations of serum UA as a continuous variable with the risks of type 2 diabetes and prediabetes. This positive association was significant when stratified by healthy weight and overweight participants. Conclusions: Serum UA levels have a graded positive association with the risks of type 2 diabetes and prediabetes among Chinese with a history of GDM.